Prospective observational study to evaluate the effect of different levels of positive end-expiratory pressure on lung mechanics in patients with and without acute respiratory distress syndrome - Fiedler-Kalenka, Mascha; Diktanaite, Dovile; Simeliunas, Emilis; Pilz, Maximilian; Kalenka, Armin (Journal of Clinical Medicine, 2020)
Background: The optimal level of positive end-expiratory pressure is still under debate. There are scare data examining the association of PEEP with transpulmonary pressure (TPP), end-expiratory lung volume (EELV) and intraabdominal pressure in ventilated patients with and without ARDS. Methods: We analyzed lung mechanics in 3 patient groups: group A, patients with ARDS; group B, obese patients (body mass index (BMI) > 30 kg/m2) and group C, a control group. Three levels of PEEP (5, 10, 15 cm H2O) were used to investigate the consequences for lung mechanics. Results: Fifty patients were included, 22 in group A, 18 in group B (BMI 38 ± 2 kg/m2) and 10 in group C. At baseline, oxygenation showed no differences between the groups. Driving pressure (ΔP) and transpulmonary pressure (ΔPL) was higher in group B than in groups A and C at a PEEP of 5 cm H2O (ΔP A: 15 ± 1, B: 18 ± 1, C: 14 ± 1 cm H2O; ΔPL A: 10 ± 1, B: 13 ± 1, C: 9 ± 0 cm H2O). Peak inspiratory pressure (Pinsp) rose in all groups as PEEP increased, but the resulting driving pressure and transpulmonary pressure were reduced, whereas EELV increased. Conclusion: Measuring EELV or TPP allows a personalized approach to lung-protective ventilation.
Gesehen am 05.10.2020